Isolation and Role of PmRGL2 in GA-mediated Floral Bud Dormancy Release in Japanese Apricot (Prunus mume Siebold et Zucc.) - Lv, Lin; Huo, Ximei; Wen, Luhua; Gao, Zhihong; Khalil-ur-Rehman, Muhammad (Frontiers in Plant Science, 2018)
Bud dormancy release is regulated by gibberellins (GAs). DELLA proteins are highly conserved and act as negative regulators in gibberellin signaling pathway. The present study established a relationship between PmRGL2 in Japanese apricot and GA4 levels during dormancy release of floral buds. Overexpression of PmRGL2 in poplar delayed the onset of bud dormancy and resulted in dwarf plants, relative to wild-type trees. PmRGL2 exhibited higher expression during ecodormancy and relatively lower expression during endodormancy. The relative level of GA4 exhibited an increasing trend at the transition from endodormancy to ecodormancy and displayed a similar expression pattern of genes related to GA metabolism, PmGA20ox2, PmGA3ox1, PmGID1b, in both Japanese apricot and transgenic poplar. These results suggests that PmRGL2 acts as an integrator and negative regulator of dormancy via a GA-signaling pathway. Moreover, an interaction between RGL2 and SLY1 in a yeast two hybrid (Y2H) system further suggests that SCF E3 ubiquitin ligases, such as SLY1, may be a critical factor in the regulation of RGL2 through an SCFSLY1-proteasome pathway. Our study demonstrated that PmRGL2 plays a negative role in bud dormancy release by regulating the GA biosynthetic enzymes, GA20ox and GA3ox1and the GA receptor, GID1b.